Research of Meshing Contact Impact Stress Distribution of Circular Arc Tooth Trace Cylindrical Gear Surface - Ma Dengqiu; Wei Yongqiao; Ye Zhenhuan; Luo Lan; Hou Li (Jixie chuandong)
In order to research the meshing contact impact stress distribution rule of the circular arc tooth trace cylindrical gear,the cause of meshing contact impact is analyzed based on gear system contact dynamics and gear physical model. Then,the accurate 3 D model is set up based on the gear tooth surface equation,and the finite element analysis models of the meshing contact impact with different impact positions are established further. Finally,the simulation analysis of the meshing contact impact under the different impact speed,which occur at different positions is carried out,the distribution rule of the gear surface meshing contact impact stress are studied. Results show that,the dangerous area of the driven gear is close to the gear root of the loaded tooth surface,when the meshing contact impact takes place in the reference circle and gear top; the dangerous area is close to the gear root of no loaded tooth surface,when the meshing contact impact takes place in the gear root.